The Challenges of Arctic Reindeer Herding: The Interface Between Reindeer Herders Knowledge and Modern Understanding of the Ecology, Economy, Sociology and Management of Sami Reindeer Herding - Eira, Inger Marie G.; Magga , O.H.; Bongo, Mathis P.; Sara, Mikkel Nils; Mathiesen, Svein D.; Oskal, Anders (2008)
Aspects of Sami reindeer husbandry, traditional knowledge, EALAT.